Problematics of Interfaith Marriage: The Interaction between Islamic Human Rights and Universal Human Rights - Abdul Mufti Albasyari; Eman Suparman (Indonesian Journal Publisher, 2026)
Marriage constitutes a sacred covenant that binds a man and a woman as husband and wife. Fundamentally, each religion prescribes its own regulations governing marriage. However, in practice, interfaith marriage remains prevalent in Indonesia and continues to generate debate, including among Muslim communities. This library-based research aims to examine how Islamic human rights and Western human rights perspectives respond to the practice of interfaith marriage in Indonesia. The findings indicate that, from the standpoint of universal human rights, the Kompilasi Hukum Islam (Compilation of Islamic Law) as the legal foundation regulating interfaith marriage in Indonesia is considered inconsistent with universal human rights principles, which are anthropocentric in nature, where the freedom to establish a family appears to be constrained. Conversely, within the framework of Islamic human rights, the prohibition of interfaith marriage as stipulated in the KHI is regarded as both justified and appropriate. In the context of family formation, Islamic human rights emphasize the primacy of religious values over anthropocentric principles. Islamic human rights not only recognize rights among human beings (huquq al-‘ibad), but also ground these rights in fundamental obligations that are inherently binding in devotion to Allah SWT (huquq Allah).